Practicality Test of Quizizz Media in Designing Instructional Problem-Based Learning on Membrane Transport Material - Arneta, Chindy; Minarti, Ipah Budi; Hartadiyati WH, Eny (Jurnal Report of Biological Education, 2025)
Background: Based on field findings and previous studies, the utilization of digital learning media such as quizizz in instructional design remains suboptimal, particularly within innovative learning models like Problem-Based Learning (PBL). Quizizz has primarily been used as an assessment tool rather than being integrated as an essential component of the instructional process. This study aims to examine the practicality of using quizizz within a PBL-based instructional design for the topic of membrane transport in high school biology. Methods: The research employed a Research and Development (R&D) method using the 4-D model, limited to the develop stage, which focuses on evaluating product practicality. A limited-scale trial was conducted involving 34 grade XI students and one teacher at SMA Negeri 2 Mranggen. A practicality perception questionnaire was used as the research instrument. Results: Quizizz integrated into PBL instructional design was perceived as practical by students, with an average score of 77.72%, and by the teacher, with an average score of 72.50%.  Conclusion: These findings indicate that quizizz is a practical tool for use in PBL-based instructional design, particularly for teaching membrane transport in high school biology classes.